Influence of public hospital reform on public health: Evidence from a quasi-natural experiment in China - Guo, Bingnan; Feng, Weizhe; Cai, Huilin; Lin, Ji (Frontiers in Public Health, 2023)
Public health is an important symbol of national wealth and prosperity. At present, China’s public health is hindered by the poor management of public hospitals, which disturbs the demographic structure and socioeconomic development. Therefore, taking the implementation of public hospital reform in China as a quasi-natural experiment, this article employs the time-varying DID model and the mediating effect to evaluate the impact of public hospital reform on public health. The results are as follows. (1) Public hospital reform can significantly improve public health, and a series of robustness tests have also confirmed the effects. (2) Government’s financial support is a transmission mechanism for public hospital reform to promote public health. (3) The effect of public hospital reform is stronger in western regions and cities with poorer economic strength after taking control variables into consideration. This research provides a vital policy reference for further promoting the scope of reform and improving the health of the general public.